Assessment of the Structural Response of Steel Reinforced and Steel-Fibre Reinforced Concrete Structures with 3D Detailed Modeling: Limitations and Remedies - Papadrakakis, Manolis; Markou, George (My University, 2022)
The assessment of the nonlinear response of existing structures, or of new structural designs, to extreme loading conditions is of significant importance in achieving a safe and sustainable built environment. The accurate prediction of structural response of steel and steel-fibre reinforced concrete structures, that are expected to undergo ultimate limit state, monotonic and cyclic loading, is a challenging task, which is hindered by numerous modeling and numerical obstacles. As a consequence to this, the assessment of retrofitted reinforced concrete structures, is still conducted with the use of simplistic numerical models and semi-empirical design formulae. Although, quite a few 3D detailed modeling approaches have been proposed over the last two decades, they have a number of limitations that prevent them from their implementation, without simplifications, to the design of steel and fiber/steel reinforced concrete structures. In this work, the capabilities as well as the limitations of the recently published work on the subject will be critically presented, while different open problems will be discussed and remedies will be proposed to overcome these limitations. Furthermore, the development of a simulation tool with the ability to accurately and efficiently predict the structural performance of new designs and assess the bearing capacity of existing or retrofitted structures under extreme loading conditions, will also be discussed.